Pengaruh Model Pembelajaran Berbasis Masalah dan Group Investigation Terhadap Hasil Belajar dan Kemampuan Berpikir Kreatif Pada Materi Sistem Pencernaan Makanan di SMA Negeri 1 Muara Batu Kabupaten Aceh Utara - Elsa Bunga Dayanti; Hasruddin Hasruddin; Syahmi Edi (Jurnal Pendidikan Biologi, 2016)
This study was aimed to determine the effect of problem based learning and group investigation on: (1) learning outcomes; and (2) creative thinking ability of student in class XI of SMAN 1 Muara Batu. This type of research is a quasi-experimental research with pretest-posttest control group design. Samples were selected using random cluster sampling technique and divided into experimental and control classes. Class XI IPA3 was applied problem-based learning model,  class XI IPA1 was applied to the model group investigation, and class XI IPA2 was applied in the conventional learning (control). Multiple choices were used to measure learning outcomes, while tests of creative thinking skills in the form of essay questions. Data were analyzed using Analysis Covarian (Anacova) at significance level α = 0.05 and followed by Tukey's test with SPSS 21.0. The results showed that: (1) There was an effect of learning model to the learning outcomes of students (F = 14.183, P = 0.000). Students who were taught by problem-based learning model was significantly different from those of group investigation and conventional learning model; and (2) There was an effect of learning model to students creative thinking abilities (F = 12.030, P = 0.000). Students who were taught by problem-based learning model was not significantly different from the group investigation model but differed significantly with students who were taught by conventional learning model.